Capacity building needs of small and medium contracting enterprises in Klang Valley Malaysia - Lee, Wah Peng; Toh, Tien Choon; Lew, Yoke Lian; Khor, Sin Huai; Goh, Kai Chen; Gui, Hun Chuen; Zainordin, Nadzirah; Lee, Chia Kuang (Penerbit Universiti Malaysia Pahang, 2020)
This study investigated the issues constraining the growth of small and medium-scale contracting firms, which can, in turn, reflect the small and medium-scale contractors’ needs that are corresponding to the needs or supports required by small and medium-scale contractors. The purpose of this study is to help SMCEs realise their own needs and also to assist government and policymakers to discover the approaches that should be executed and allocate scarce resources to the critical parts through needs identification and appraisal. A closed-ended questionnaire survey was deployed and the responses collected only reflecting the construction players that are currently working in CIDB registered Grade 1 to Grade 6 contracting enterprises in the Klang Valley area. Through factor analysis, five critical needs have been identified. They are technical and technological needs, job accessibility needs, favourable fiscal and monetary policy needs, business development needs and anti-corruption needs. Besides, this study revealed that the success of SMCEs can be perceived in the aspects of their business growth, profit growth and employment growth. Research studies on this topic are limited in the Malaysian construction industry. Therefore, this study provides guidance and references for SMCEs and policymakers concerning the capacity building needs and how their successes can be achieved so that SMCEs can be assisted in a way that is truly able to build their capabilities in today’s construction sector in Malaysia.